Impresiones de intimidad y de goce en tres poemas de Carmen Naranjo: América/Hacia tu isla/Canción de la ternura - Borloz Soto, Virginia (2014)
This article consists of an interpretative reading of three poems from Carmen Naranjo (Costa Rica, 1931-2012). Due to these creations she introduces herself into Costa Rican literary world, and at the same time she begins a long journey through Latin American literature. The author of this article intends to present a particular reading about what Naranjo’s poetry could provoke during the process of reception.